TUTURAN IMPERATIF DALAM SERIAL KOMEDI MALAM MINGGU MIKO - Efarianti, Deka; Hakim, Nursal; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study entitled Imperative utterances in a Malam Minggu Miko comedy series. This study aimed to describe the form and meaning of the imperative in Malam Minggu Miko comedy series. The research is a qualitative research with descriptive methods. This research data is the form and meaning of speech imperatives contained in Malam Minggu Miko comedy series. Data obtained using the technique of listening and listening. The validity of the data obtained by a triangulation technique. Then, the data were analyzed by identifying and classifying based on the nature and meaning of the imperative in the speech. The results of the research I have found in this study is that there are six imperatives form contained in Malam Minggu Miko comedy series is the imperative form of regular, demand, licensing, solicitation, errands, and prohibition. Among the imperative form, the predominant form found is imperative messenger. In the study of meaning, the author uses seventeen kinds of meaning imperative. Impertif dominant meaning is found is the meaning of pragmatic imperative command.Key Words: narrative imperative, Malam Minggu Miko comedy series, the imperative form of speech, the meaning of the imperative